Role of RFRP-3 in the Regulation of Kiss-1 Gene Expression in the AVPV Hypothalamic Cell Model mHypoA-50. (September 2019) - Kanasaki, Haruhiko; Tumurbaatar, Tuvshintugs; Oride, Aki; Tumurgan, Zolzaya; Okada, Hiroe; Hara, Tomomi; Tsutsui, Kazuyoshi; Kyo, Satoru
Kisspeptin, encoded by the Kiss-1 gene, plays a crucial role in reproductive function by governing the hypothalamic–pituitary–gonadal axis. The recently established Kiss-1-expressing cell model mHypoA-50 displays characteristics of neuronal cells of the anteroventral periventricular (AVPV) region of the mouse hypothalamus. Because Kiss-1 gene expression in these cells is upregulated by estradiol (E2), mHypoA-50 cells are regarded as a valuable model for the study of Kiss-1-expressing neurons in the AVPV region. These cells also express RFamide-related peptide-3 (RFRP-3), a mammalian homolog of gonadotropin inhibitory hormone. The RFRP-3 expression in mHypoA-50 cells was increased by melatonin stimulation. In addition, E2 stimulation increased RFRP-3 expression in these cells. Treatment of the mHypoA-50 cells with exogenous RFRP-3 resulted in the increase of Kiss-1 messenger RNA expression within the cells; however, RFRP-3 did not modify gonadotropin-releasing hormone or kisspeptin-induced Kiss-1 gene expression in these cells. In addition, we found that RFRP-3 stimulation increased the expression of corticotropin-releasing hormone, which may be involved in E2-induced positive feedback in mHypoA-50 cells. Our observations suggest that RFRP-3 might be involved in positive feedback regulation by directly or indirectly increasing Kiss-1 gene expression.